Estrategias y oportunidades de cambio y mejora de los servicios sociales municipales - Brezmes Nieto, María Jesús (Miscelánea Comillas, 2010)
This article is essential statements that form a framework approach onsocial services and the role of local authorities. Try to identify, first, the reason for the municipal social services in the context of a social service system, which highlights its internal problems before the processes of social change, organizational, economic and technological development. Secondly, we briefly describethe trends of the environment and the position of social service organizations and the progress made in them. The third section outlines the proposed content in strategic management, quality and information and communication technologies, to move to propose a basic approach to simplify the structure of the municipal social services, and organization of services and equipment. Finally, indicate the need for sufficient budget, indicating very briefly funding sources.